LAYANAN INFORMASI BIMBINGAN KONSELING MEMUDAHKAN SISWA/I MEMILIH PERGURUAN TINGGI DAN PROGRAM STUDI SESUAI MINAT DAN KEMAMPUAN PADA SISWA/I KELAS XII IPA3 SMAN 1 PULAU PUNJUNG KABUPATEN DHARMASRAYA - Ramadhanis, Ramadhanis (Inovasi Pendidikan, 2019)
Action Research This service leads more to career guidance and counseling, aimed at facilitating the development, exploration, aspiration and career decision making throughout the life span of students / counseling. The research subjects were students of class XII IPA 3 at SMAN 1 Pulau Punjung using an open questionnaire in which respondents gave freedom in giving choice answers according to knowledge. In the first cycle of counseling information services carried out 3 students the same or 15% of 20 students / i the condition is quite good level (11-15), and 14 students or 70% of 20 students / i are in poor condition ( 10), 3 students or 15% of 20 students / conditions are in a good level (16-20). In the second cycle, the results of 16 people were drawn or 80% of the 20 students were at a level capable of making decisions to choose universities and study programs in accordance with their interests and abilities with good quality. In the second cycle of the results of the observation the average value of students achieve good quality. In the second cycle the results of reflection III showed a success rate of 18 people or 90% of the 20 students / conditions were at a level capable of making decisions to choose colleges and study programs according to their interests and abilities with good quality (16-20), and 2 people or 10 % of 20 students / i, are very capable of making decisions to choose universities and study programs with good quality.Keywords: Election decision making, universities and study programs, information services